2020
DOI: 10.5194/os-2020-38
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of a medicane on the oceanic surface layer from a coupled, kilometre-scale simulation

Abstract: Abstract. A kilometre-scale coupled ocean-atmosphere numerical simulation is used to study the impact of the 7 November 2014 medicane on the oceanic upper layer. The processes at play are elucidated through analyses of the tendency terms for temperature and salinity in the oceanic mixed layer. Whereas comparable by its maximum wind speed to a Category 1 tropical cyclone, the medicane results in a substantially weaker cooling. As in weak to moderate tropical cyclones, the dominant contribution to the su… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
2
1
0
Order By: Relevance
“…Lebeaupin Brossier et al, 2009Rainaud et al, 2017) and is comparable to other high-wind or medicane events (e.g. Renault et al, 2012;Bouin and Lebeaupin Brossier, 2020a be underestimated by the model (−0.6°C in 24 hours and −0.85°C in 42 hours simulated by AOW). Overall, this default in representing the cooling can be explained by the initial ocean state with a too smooth thermocline that limits the mixed-layer cooling by entrainment, by physical parameters and/or schemes in NEMO and by the absence of ocean-wave coupling.…”
Section: Atmosphere-ocean Couplingsupporting
confidence: 66%
“…Lebeaupin Brossier et al, 2009Rainaud et al, 2017) and is comparable to other high-wind or medicane events (e.g. Renault et al, 2012;Bouin and Lebeaupin Brossier, 2020a be underestimated by the model (−0.6°C in 24 hours and −0.85°C in 42 hours simulated by AOW). Overall, this default in representing the cooling can be explained by the initial ocean state with a too smooth thermocline that limits the mixed-layer cooling by entrainment, by physical parameters and/or schemes in NEMO and by the absence of ocean-wave coupling.…”
Section: Atmosphere-ocean Couplingsupporting
confidence: 66%
“…Lebeaupin Brossier et al, 2009Rainaud et al, 2017) and is comparable to other high-wind or medicane events (e.g. Renault et al, 2012;Bouin and Lebeaupin Brossier, 2020a be underestimated by the model (−0.6°C in 24 hours and −0.85°C in 42 hours simulated by AOW). Overall, this default in representing the cooling can be explained by the initial ocean state with a too smooth thermocline that limits the mixed-layer cooling by entrainment, by physical parameters and/or schemes in NEMO and by the absence of ocean-wave coupling.…”
Section: Atmosphere-ocean Couplingsupporting
confidence: 66%
“…Gaertner et al (2017) suggested that the effects of air-sea interaction on medicanes may depend on the oceanic mixed layer depth, while Ricchi et al (2017) found that the surface roughness from wave motion significantly affected the November 2011 case. Bouin and Lebeaupin Brossier (2020) identified strong control of sea-surface temperature (SST) on latent heat fluxes, which maintained convection in the November 2014 case. Miglietta et al (2011) and Pytharoulis (2018) investigated the impact of a uniform SST change for two different medicanes (September 2006 andNovember 2014), agreeing that warmer (colder) SSTs lead to more (less) intense cyclones, but only for changes above ±2 • C.…”
Section: Introductionmentioning
confidence: 99%